Position and Role of the Secretariat of the Tanah Datar Regency DPRD in the Formation of Regional Regulations for the 2019-2024 Period - Ira Tri Dewi; Darmini Roza; Zennis Helen (Master of Law Program, Ekasakti University, 2025)
This study analyzes the position and role of the Secretariat of the Tanah Datar Regency DPRD in the formation of Regional Regulations (Perda) for the 2019–2024 period and identifies the obstacles faced in the implementation of these functions. The research is descriptive-analytical with a normative juridical approach supported by empirical data through a field study at the Secretariat of the Tanah Datar Regency DPRD, using secondary and primary data that are analyzed qualitatively. The results of the study show that the DPRD Secretariat has a tactical and vital position: technically it is under and responsible to the leadership of the DPRD, while administratively it is under and responsible to the regent through the regional secretary. In the formation of the Regional Regulation, the Secretariat of the DPRD carries out administrative and technical functions which include secretarial management, finance, meeting facilitation, preparation of academic manuscripts, provision of legal opinions, provision of experts, and the archiving and publication of regional legal products based on the attribution authority and mandate given by laws and regulations. The study also found four main obstacle groups, namely the limitation of competent human resources in the field of legislation, lack of technical support facilities and infrastructure, the absence of SOPs and standard legislation timelines, and coordination between institutions that are not optimal, which overall hinder the effectiveness of the functions of the DPRD Secretariat and the quality of regional legislation performance within the framework of regional autonomy.